Polyphenols from Food and Natural Products: Neuroprotection and Safety - Rui F. M. Silva; Lea Pogačnik (MDPI AG, 2020)
Polyphenols are naturally occurring micronutrients that are present in many food sources. Besides being potent antioxidants, these molecules may also possess anti-inflammatory properties. Many studies have highlighted their potential role in the prevention and treatment of various pathological conditions connected to oxidative stress and inflammation (e.g., cancer, and cardiovascular and neurodegenerative disorders). Neurodegenerative diseases are globally one of the main causes of death and represent an enormous burden in terms of human suffering, social distress, and economic costs. Recent data expanded on the initial antioxidant-based mechanism of polyphenols’ action by showing that they are also able to modulate several cell-signaling pathways and mediators. The proposed benefits of polyphenols, either as protective/prophylactic substances or as therapeutic molecules, may be achieved by the consumption of a natural polyphenol-enriched diet, by their use as food supplements, or with formulations as pharmaceutical drugs/nutraceuticals. It has also been proved that the health effects of polyphenols depend on the consumed amount and their bioavailability. However, their overconsumption may raise safety concerns due to the accumulation of high levels of these molecules in the organism, particularly if we consider the loose regulatory legislation regarding the commercialization and use of food supplements. This review addresses the main beneficial effects of food polyphenols, and focuses on neuroprotection and the safety issues related to overconsumption.